Secure AODV Routing Strategies in Smart Cities for Vehicular Communication - Fadhil A.M.; Din N.M.; Aripin N.B.M.; Abed A.A. (International Information and Engineering Technology Association, 2025)
Vehicular Ad hoc Networks (VANETs) have become prominent in the past few years for the transportation sector. Vehicular mobility poses a significant challenge for establishing private communications in VANETs. The classical Ad hoc On-Demand Distance Vector (AODV) routing protocol used in VANET assumes that all nodes are non-malicious. To address this matter, this paper proposes making AODV routing protocols more secure by using a privacy scheme in AODV for vehicle-to-vehicle communication. The AODV privacy scheme tries to keep the automobile network connected reliably and stably during communication with the secured transmission of messages and minimize the risk of unauthorized access to sensitive information from eavesdropper attacks. The proposed privacy secure AODV routing named PSAODV used pseudonym changes in vehicle communication to hide the target vehicle's location. A VANET simulator based on OMNET++ and SUMO are used for evaluating the PSAODV routing protocol. A simulation study was conducted that compared the PSAODV with SE-AOMDV, ECC-AODV, and AODV in fundamentals of efficiency and confidentiality. The analysis results showed that PSAODV routing demonstrates routing efficiency with privacy by diminishing the effect of eavesdropping of vehicles information based on various scenarios in urban cities. Copyright: ?2024 The authors.